2020
DOI: 10.1590/s0004-2803.202000000-59
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of Anti-TNF Use in the Era of New Biological Agents in Inflammatory Bowel Disease

Abstract: BACKGROUND: Inflammatory bowel diseases (IBD), both Crohn’s disease and ulcerative colitis, are chronic immune-mediated diseases that present a relapsing and remitting course and requires long-term treatment. Anti-tumor necrosis factor (anti-TNF) therapy has changed the management of the disease by reducing the need for hospitalizations, surgeries and improving patient´s quality of life. OBJECTIVE: The aim of this review is to discuss the role of anti-TNF agents in IBD, highlighting the situations where its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…Based on the view of effective risk reduction, we spotted the data from a multicenter study from America suggesting that exposure to anti-TNFα agents in UC patients is associated with a reduction in CRC risk after adjustment for possible confounding factors (OR 0.78, 95% CI 0.73–0.83, p < 0.0001) [ 14 ], which was confirmed in other studies additionally [ 178 , 179 ]. Although anti-TNF has acceptable safety profiles, there are concerns about the risk of adverse events, including infections, malignancy, metabolic and immunological diseases [ 180 ]. Moreover, other drugs such as Ustekinumab targeted IL-12/IL23, Vedolizumab targeted integrin α4β7 and Tofacitinib targeted JAK are approved to treat UC [ 181 , 182 , 183 ].…”
Section: Chemoprevention Of Crc In Ucmentioning
confidence: 99%
“…Based on the view of effective risk reduction, we spotted the data from a multicenter study from America suggesting that exposure to anti-TNFα agents in UC patients is associated with a reduction in CRC risk after adjustment for possible confounding factors (OR 0.78, 95% CI 0.73–0.83, p < 0.0001) [ 14 ], which was confirmed in other studies additionally [ 178 , 179 ]. Although anti-TNF has acceptable safety profiles, there are concerns about the risk of adverse events, including infections, malignancy, metabolic and immunological diseases [ 180 ]. Moreover, other drugs such as Ustekinumab targeted IL-12/IL23, Vedolizumab targeted integrin α4β7 and Tofacitinib targeted JAK are approved to treat UC [ 181 , 182 , 183 ].…”
Section: Chemoprevention Of Crc In Ucmentioning
confidence: 99%
“…Approximately one-third of patients may have a primary nonresponse to an initial agent. Secondary loss of response, after initial improvement, is also frequent in the management of CD and UC [ 6 , 7 ]. Data on genetic and microbiological signatures and new biomarkers are needed in order to guide this appropriate medication choice [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for this decline was the reduction in mortality from cardiac causes. 25 Similarly, Lima et al, 22 reported that the mortality rate in patients with CD treated with infliximab was similar to that in patients receiving other treatments. Regarding adalimumab, studies have reported no increased mortality rate associated with treatment of RA, AS, psoriasis, PsA, or CD compared with a matched control population.…”
Section: Safety Of Anti-tnf Medicationmentioning
confidence: 87%
“…Though the safety profile of anti-TNFs is generally considered to be acceptable in relation to the associated benefits, 22,23 there remains concern 22 regarding potential associations with infection, malignancy, and immunogenicity. 21 Safety data should be assessed alongside the known risks of IMIDs themselves of concomitant medication such as non-steroidal anti-inflammatory drugs 24 and of non-treatment of the condition in question.…”
Section: Safety Of Anti-tnf Medicationmentioning
confidence: 99%